Do semi-natural habitats enhance overwintering of generalist predators in arable cropping systems? A meta-analysis(Research data gouv) - Paul Bannwart; Antoine Gardarin; Sandrine Petit (Biological Control)
The enhancement of invertebrate generalist predator populations through habitat management is a promising way to control pest populations and could contribute to pesticide use reduction in arable agriculture. The majority of studies on invertebrate ground-dwelling predators are focusing on the activity-density of adults during their period of activity and provide limited insight into their overwintering ecology. Semi-natural habitats (SNH) are frequently considered as key winter refuge but their contribution is often not compared with the contribution of adjacent arable crops. We performed a meta-analysis to investigate whether SNH are key overwintering sites relatively to adjacent crops, for two abundant and widespread generalist predator groups in agroecosystems: carabid beetles and spiders. We identified a corpus limited to 19 studies and 114 comparisons between SNH (linear or patch) and arable crops (autumn-sown and spring-sown crops) that monitored predators with traps avoiding predator movement during their overwintering. Our analysis revealed that SNH significantly sheltered higher densities of overwintering spiders than adjacent crops. Concerning carabid populations, densities of overwintering carabids were influenced by the shape of SNH with higher overwintering densities in linear elements (grass strips, flower strips, hedges) than in arable crops. In addition, carabid overwintering density and diversity were higher in SNH when the adjacent crop was a spring-sown crop, indicating a higher sensitivity to agricultural disturbances or low trophic resources. These findings highlight the predator and agricultural context-dependent role of semi-natural habitats as overwintering refuge and underline the increased consideration that should be granted to autumn-sown crops as suitable overwintering habitat.